2015
DOI: 10.1007/s10439-015-1488-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Three-Dimensional Distribution and Clustering of Intramuscular Fat in Muscles of the Rotator Cuff

Abstract: The purpose of this study was to 1) develop and present a technique to quantitatively assess three-dimensional distribution and clustering of intramuscular fat and 2) use the technique to compare spatial characteristics of intramuscular fat in rotator cuff muscles of older adults with and without a supraspinatus tear. Moran’s Index (I), an existing quantitative measure of clustering, was extended for use with MRI to allow comparisons across individuals with different size muscles. Sixteen older adults (>60yrs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…29 In clinical and animal studies, infiltrated fat was proved to be distributed closer to the torn muscle–tendon unit than throughout the muscle belly. 29,42,50 Similarly, on the basis of our reconstructed 3D fat map in patients, we found that high fatty infiltration was inhomogeneously distributed close to the distal muscle (Figure 6), which may result in significant differences between 2D-FF and 3D-FF.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…29 In clinical and animal studies, infiltrated fat was proved to be distributed closer to the torn muscle–tendon unit than throughout the muscle belly. 29,42,50 Similarly, on the basis of our reconstructed 3D fat map in patients, we found that high fatty infiltration was inhomogeneously distributed close to the distal muscle (Figure 6), which may result in significant differences between 2D-FF and 3D-FF.…”
Section: Discussionmentioning
confidence: 58%
“…36,54,55 Researchers attempted to obtain 3D-FF by averaging the FF of 3 sagittal planes or adding FFs in all MRI slices; however, the debate has intensified about the differences between 2D-FF and 3D-FF and whether 2D-FF can represent 3D-FF. 23,36,50,52,54 Vidt et al 54 compared the single sagittal slice–based fatty infiltration scores and all slice–summed 3D-FF and concluded that FF on a single image slice does not represent 3D-FF. In contrast, Lee et al 36 calculated 3D-FF by averaging FF from 3 single sagittal slices and reported that 2D-FF could be equal to 3D-FF.…”
mentioning
confidence: 99%
“…The standard Dixon imaging sequence allowed the signal for each voxel to be separated into signal intensity from fat and water, from which a fat percentage was available for each voxel according to equation 1, which generated the intramuscular fat fraction within the outlined area of the SSP (SSP area_i on each slice [FF i ]) automatically to reflect layer FI within the SSP area (Figure 1A). 21,28 Fat % ð Þ5 Fat signal ðFat signal 1 water signalÞ…”
Section: Global-fi Measurements In the Whole Sspmentioning
confidence: 99%
“…They reported no neuromuscular changes between their groups [27]. Another contributing factor to muscle activation physiology in patients with chronic supraspinatus tears is the possibility of increased intramuscular fat content and clustering at the distal end of the muscle [34]. This factor and tear size are both indicators of postoperative success and surgical indicators in our study population.…”
Section: Discussionmentioning
confidence: 63%
“…This factor and tear size are both indicators of postoperative success and surgical indicators in our study population. Because our population consisted of full‐thickness or near–full‐thickness tears of the supraspinatus, these individuals would be at risk for intramuscular fat developing distally [34,35]. The single surgeon responsible for the repairs in the RC population did not observe fatty degeneration, and reported that tear sizes of 2 cm or less in the anterior/posterior direction (Table 1) were small enough to be repaired with minimal risk of postoperative failure.…”
Section: Discussionmentioning
confidence: 99%